Parasocial Intimacy, Perceived Authenticity, and Scarcity Prestige in Creator-Led Commerce: Drivers of Premium Food Purchase Decisions - Kadek Indira Savitiri; Dewi Alesha Miller (Ilomata International Journal of Social Science, 2026)
This study examines purchase decision making in creator led premium food commerce by analysing how parasocial intimacy, perceived authenticity, and product scarcity shape consumer behaviour in Indonesia’s influencer driven market. Despite high prices and limited functional differentiation, creator led products often generate strong demand, yet empirical explanations remain limited. This study addresses how symbolic and psychological factors translate into purchase decisions within this context. Extending social commerce and influencer marketing literature, this research integrates parasocial intimacy, perceived authenticity, and scarcity prestige within a single model, with intention to purchase as a mediating variable. Data were collected from 420 social media users aged 20 to 45 in Jakarta and analysed using Partial Least Squares Structural Equation Modelling. The results indicate that intention to purchase has a strong and significant effect on purchase decisions, while parasocial intimacy, perceived authenticity, and product scarcity influence purchase decisions only indirectly through intention, indicating full mediation. These findings suggest that premium food consumption in creator led markets follows a deliberative pathway rather than a purely impulsive one, where emotional closeness, authenticity perceptions, and credible scarcity cues must first shape purchase intention before translating into behaviour. This study highlights the central role of intention formation in premium social commerce and provides strategic implications for creators and brands to prioritise authentic relationships and credible value construction over direct sales pressure.